KEDUDUKAN DAN EKSISTENSI TENAGA KERJA OUTSOURCING DALAM DUNIA BISNIS - Fontian Munzil (Media Nusantara, 2011)
Manpower needs of the fast condition with a homogen competence in large numbers are needed by many business industries such as manufacturing or the financial services institution. Labor laws reach out the existence of workers provided by employment service providers who can meet the manpower needs of an enterprise. Outsourcing manpower was limited the scope of work to do work that is not a core business / main activities of the respective companies where if the work is done by outsourcing according of the labor law , labor relations status with the company's outsourcing services provider to switch to a working relationship with the employer company . Agreement on which the based of the parties with the object law is an outsourcing labor is not to violate the conditions of validity of the agreementthatis an objective requirement of thejob is the responsibility of the outsourcing of labor is not the main activity of companies using outsourced labor